Extreme Production Conditions of Photovoltaic Power Plant Operated in Distribution Grid - Martin Smocek; Zdenek Hradilek (Advances in Electrical and Electronic Engineering, 2014)
Photovoltaic power plants are sources of electrical energy that are very dependent on weather conditions. This paper interests in description of stochastic production of power in photovoltaic power plants and subsequently its impact on the distribution power grid. Stochastic production of power from these sources is considerable and hardly predictable. The aim of this survey is to assess the influence of photovoltaic power plants operation on the daily load diagram with regard to output change difference of active power at the relevant substation. Evaluation is based on real-time synchronous data measuring both on-site photovoltaic power plant operation and on-site electric power line output from the substation. This measurement is used for suggestion of a general calculation methodology for the assessment of the difference of active power at a particular node of the grid under various power changes from the photovoltaic power plant. Statistical methods have been employed to process a methodology in order establish extreme conditions of production power for photovoltaic power plant.